Postharvest Bee Diversity is High but Declines Rapidly with Stand Age in Regenerating Douglas-Fir Forest. Issue 3 (25th March 2021) - Rivers, James W; Betts, Matthew G
Abstract: Concerns about long-term pollinator declines have made assessing bee communities a priority in nonagricultural ecosystems, including managed forests. We assessed wild bee communities in Douglas-fir ( Pseudotsuga menziesii [Mirb.] Franco) stands one to 15 years after clearcut harvest in western Oregon, USA, testing the hypothesis that bee diversity would be high initially and then decline with time-dependent reductions in floral resources. We captured 2, 009 individual bees that represented 67 distinct species/morphospecies in 20 genera and five families. Asymptotic estimators of bee diversity representing Shannon and Simpson diversity were greater in communities during the second half of the early seral period, indicating older early seral stands were less diverse and contained more common and dominant bee species. In addition, observed species richness and bee abundance peaked at approximately three years postharvest and declined thereafter by 20% and 30% per year, respectively. Because floral resources declined in concert with reductions in bee diversity as stands aged, food appears to be a key driver of forest bee communities. Our results indicate that postharvest Douglas-fir stands supported a diversity of bees, including important crop pollinators, but their value to bees was restricted to a relatively short window at the beginning of the early seral period.